Sociology Teacher Strategies in Implementing Differentiated Learning in Makassar City High Schools - Sadriani, Andi (Peneliti.net, 2023)
Differentiated learning is one strategy that teachers can use to meet the needs of each student. Differentiation is a teaching and learning process in which students learn subject matter based on their abilities, what they like, and their individual needs so that they are not frustrated and feel like failures during the learning process. This research uses a type of qualitative research with a case study approach that focuses on the teacher's strategic phase in applying differentiated learning. The informants in this study were Sociology teachers from various backgrounds from both public and private schools. Data were collected through in-depth interviews, and observations made during the differentiated learning process were applied by teachers. The data obtained is then analyzed through three stages of validation using source triangulation techniques. The results of the study found that there are at least 5 strategies used by Sociology teachers in applying differentiated learning to Sociology subjects.